Biochemical methods for producing and characterising recombinant spider silks - Anton Maraldo; Anton Maraldo; James H. Torpey; Sasha L. Evans; Aditya Rawal; Jeffery L. Yarger; Rivka L. Isaacson; Christopher P. Marquis; Christopher P. Marquis; Sean J. Blamires; Sean J. Blamires (Frontiers in Arachnid Science)
Here, we review the processes involved in producing and assessing the quality of recombinant spider silk proteins (spidroins) and the challenges associated with their synthesis and spinning into robust fibres. We provide an overview of the techniques used to produce the proteins, from gene synthesis to expression in various host organisms. Evidence suggests that the N- and C-terminal regions of spidroins are of utmost importance for fibre assembly and the repetitive domains are responsible for the unique mechanical properties in both native and recombinant versions of spider silks. We describe the role of liquid–liquid phase separation (LLPS) in spidroin assembly and its importance in subsequent fibre formation. Recent developments in recombinant spidroin production and co-expression strategies for improving yield and scalability are highlighted. Techniques such as mass photometry and size exclusion chromatography (SEC) for analysing protein purity and assembly behaviour are thereupon detailed. Finally, we address the role that predictive computational methods play in the future of designing novel and high-performing materials inspired by spidroins.